Detection of fusion events by RNA sequencing in FFPE versus freshly frozen colorectal cancer tissue samples - Sorokin, Maxim; Lyadov, Vladimir; Suntsova, Maria; Garipov, Marat; Semenova, Anna; Popova, Natalia; Guguchkin, Egor; Heydarov, Rustam; Zolotovskaia, Marianna; Zhao, Xiaowen; Yan, Qing; Wang, Ye; et al. (Frontiers in Molecular Biosciences, 2025)
Gene fusion events result in chimeric proteins that are frequently found in human cancers. Specific targeted therapies are available for several types of cancer fusions including receptor tyrosine kinase gene moieties. RNA sequencing (RNAseq) can directly be used for detection of gene rearrangements in a single test, along with multiple additional biomarkers. However, tumor biosamples are usually formalin-fixed paraffin-embedded (FFPE) tissue blocks where RNA is heavily degraded, which in theory may result in decreased efficiency of fusion detection. Here, for the first time, we compared the efficacy of gene fusion detection by RNAseq for matched pairs of freshly frozen in RNA stabilizing solution (FF) and FFPE tumor tissue samples obtained from 29 human colorectal cancer patients. We detected no statistically significant difference in the number of chimeric transcripts in FFPE and FF RNAseq profiles. The known fusion KANSL1-ARL17A/B occurred with a high frequency in 69% of the patients. We also detected 93 new fusion genes not mentioned in the literature or listed in the ChimerSeq database. Among them, 11 were found in two or more patients, suggesting their potential role in carcinogenesis. Most of the fusions detected most probably represented read-through, microdeletion or local duplication events. Finally, in one patient, we detected a potentially clinically actionable in-frame fusion of LRRFIP2 and ALK genes not previously described in colorectal cancer with an intact tyrosine kinase domain that can be potentially targeted by ALK inhibitors.